2014
DOI: 10.1123/ijsnem.2013-0122
|View full text |Cite
|
Sign up to set email alerts
|

Water Intake Accelerates Parasympathetic Reactivation After High-Intensity Exercise

Abstract: The results suggest that WI accelerates the postexercise parasympathetic reactivation after high-intensity exercise. Such outcome reveals an important cardioprotective effect of WI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…During this period, the risk of mortality by coronary heart disease has been found to be two to 10 times higher for firefighters engaged in firefighting activities in comparison with other on‐duty activities . Different methods have been proposed to improve parasympathetic reactivation after high‐intensity exercise, such as cold‐water immersion or water intake . Future research studies using real interventions are required to confirm the results of the present study.…”
Section: Perspectivessupporting
confidence: 55%
See 1 more Smart Citation
“…During this period, the risk of mortality by coronary heart disease has been found to be two to 10 times higher for firefighters engaged in firefighting activities in comparison with other on‐duty activities . Different methods have been proposed to improve parasympathetic reactivation after high‐intensity exercise, such as cold‐water immersion or water intake . Future research studies using real interventions are required to confirm the results of the present study.…”
Section: Perspectivessupporting
confidence: 55%
“…2 Different methods have been proposed to improve parasympathetic reactivation after high-intensity exercise, such as cold-water immersion 44 or water intake. 45 Future research studies using real interventions are required to confirm the results of the present study. Additional research studies are encouraged to investigate the influence of a recovery protocol on the autonomic nervous system recovery and the risks of mortality.…”
Section: Marcel-millet Et Almentioning
confidence: 56%
“…It has been proven repeatedly that water intake accelerates parasympathetic activation. 37,38 HF specifically reflects parasympathetic nervous system activity, which was found to increase significantly post-WDT in this study. There was also significant correlation between SCAR and HF; HF increased and HR decreased concurrently at 15-minutes post-WDT, and there was a negative correlation between HF and HR (r ¼ À0.6115; P ¼ 0.0002), which indicated that activation of parasympathetic nerves might be involved in the collapse of SC during the WDT.…”
Section: Discussionmentioning
confidence: 84%
“…However, Peçanha et al 37 and Kawano et al 38 found a positive effect of water consumption on vagal activity after moderate-to-high intensity exercise. These authors have suggested that a vagal activity increase post-WDT occurs to counterbalance a potential sympathetic pressor effect evoked by exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Vagal dysfunction appears to be associated with the onset of cardiovascular disease 2 in addition to being an important predictor for sudden death [2][3][4][5] . Thus, several research groups have dedicated themselves to investigating the effects of different variables on CVA, among which water intake is prominent [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%